The influence of tai chi on the death anxiety of elderly people living alone: the chain mediating effect of social support and psychological capital - Zhou, Jiali; Wu, Baoyuan; Su, Lining; Ma, Xiujie (Frontiers in Psychology, 2024)
Background: Population ageing is a global trend, and the number of older adults living alone is increasing. Tai chi, a traditional Chinese exercise, has been shown to improve older adults' physical and mental health. Aim: To investigate the effects of tai chi on death anxiety in older adults living alone and the role of social support and psychological capital in this relationship.A cross-sectional study of 493 older adults living alone in four cities in southwestern China. Participants were assessed using questionnaires on tai chi practice, social support, psychological capital, and death anxiety. Results: Tai chi practice significantly reduced death anxiety in older adults living alone. It also positively correlated with social support and psychological capital, both of which negatively correlated with death anxiety. Social support and psychological capital mediated the relationship between tai chi practice and death anxiety, suggesting that tai chi may reduce death anxiety through these factors. These findings encourage older adults living alone to practice tai chi, as it may improve their mental and physical health and reduce their risk of death anxiety. Conclusion: Tai chi practice may reduce death anxiety in older adults living alone through the chain-mediated effects of social support and psychological capital. This suggests that tai chi may be a beneficial intervention for older adults living alone.